2006
DOI: 10.1016/j.bbamem.2006.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Ala-504 is a determinant of substrate binding affinity in the mouse Na+/dicarboxylate cotransporter

Abstract: The Na + /dicarboxylate cotransporters from mouse (mNaDC1) and rabbit (rbNaDC1) differ in their ability to handle adipate, a six-carbon terminal dicarboxylic acid. The mNaDC1 and rbNaDC1 amino acid sequences are 75% identical. The rbNaDC1 does not transport adipate and only succinate produced inward currents under two-electrode voltage clamp. In contrast, oocytes expressing mNaDC1 had adipate-dependent inward currents that were about 60% of those induced by succinate. In order to identify domains involved in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The amino acid at position 509/512 is also involved in binding other substrates. In a study of mouse NaDC1, we found that serine replacement of the equivalent position at Ala-504, produced a more rabbit-like phenotype with decreased affinity for succinate and adipate, although the reverse mutation in rabbit (rbS512A) was not sufficient to increase affinity for adipate (18). The S512C mutant of rbNaDC1 was not expressed on the cell surface, possibly because of protein misfolding (10).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The amino acid at position 509/512 is also involved in binding other substrates. In a study of mouse NaDC1, we found that serine replacement of the equivalent position at Ala-504, produced a more rabbit-like phenotype with decreased affinity for succinate and adipate, although the reverse mutation in rabbit (rbS512A) was not sufficient to increase affinity for adipate (18). The S512C mutant of rbNaDC1 was not expressed on the cell surface, possibly because of protein misfolding (10).…”
Section: Discussionmentioning
confidence: 98%
“…The hydroxyl group of serine or threonine does not appear to be required for function since the mouse NaDC1 contains alanine at this position, and the S512A mutant of rbNaDC1 does not exhibit any change in functional properties (18). Possibly the size or volume of the side chain at this position affects the substrate binding site in NaDC1.…”
Section: Discussionmentioning
confidence: 99%
“…These include, in rabbit NaDC1, Lys-84 (22), four amino acids around Ser-260 (transmembrane helix H5), Arg-349 (H7), Asp-373 (H8), Glu-475 (H9) (summarized in Ref. 20), and Ser-512 (H10) (19). Thus, it is mainly the COOH-terminal part of NaDC3 that is involved in binding and transporting dicarboxylates.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic constants for SdcS under the above-mentioned conditions were determined for each of three independent trials and are reported in the text as means Ϯ standard errors. Such substrate preference differences within the DASS family are well documented (5,8,24,25,31) and imply that the binding pockets of these transporters have diverged sufficiently to accommodate compounds that deviate slightly from the substrate template structure.…”
Section: Purification and Reconstitution Of Functional Sdcsmentioning
confidence: 95%